TEACHERSâ DEMOTIVATION IN ENGLISH LANGUAGE TEACHING: CAUSES AND SOLUTIONS - AGUSTIANI, MERIE (Sriwijaya University Learning and Education International Conference, 2016)
Teaching and learning process is the core of education that determines the quality of education. Therefore, if there is a quality decrease of education, the first thing that should be evaluated is its teaching and learning process quality. EF-EPI (English First- English Proficiency Index) in 2014 released that Indonesian score was 52.74 which was far from the highest score. In addition, EFA global monitoring report of UNESCO (2014) also points out that Indonesia belongs to ten countries which account 72% of the global population of illiterate adults. Those results show that quality of education in Indonesia still dissatisfied. The quality of teaching and learning process depends on three aspects; (1) the studentsâ participation level on learning activities, (2) teachersâ roles in teaching and learning process, (3) learning environment. The second aspect is considered as crucial thing focussed by the experts since teacher is the manager and leader of learning process. Recently, not only studentsâ motivation but also teachersâ motivation affects studentsâ academic achivement. It is assumed that dissatified results of Indonesian education quality is caused by demotivation of teachers. This paper is aimed at discussing the causes and solutions of teachersâ demotivation in ELT.